ANALISIS IMPLEMENTASI KEBIJAKAN JAMINAN PERSALINAN DALAM MENINGKATKAN CAKUPAN PERSALINAN TENAGA KESEHATAN DI KABUPATEN SITUBONDO TAHUN 2013 - Gurendro Putro (Jurnal Kebijakan Kesehatan Indonesia, 2013)
Background:The policy of Maternity Benefit for the Uninsured(Jampersal) is based on the philosophy to reduce maternalmortality and infant. The Minister of Health Regulation number2562/Menkes/Per/XII/2011 on A Maternity Benefit for theUninsured Persons’s Technical Guidelines ensures that thegovernment provides services to pregnant women withantenatal care (ANC), parturition and post-parturition for free,including the use of contraceptives post parturition.Objective:To know the confidence’s level of pregnant womenin seeking help for parturition from the health provider, theprovider commitment to Jampersal policy, and Jampersalsocialization in the community.Methods: Cross-sectional and purposive sampling are usedfor descriptive analysis. Data collection is conducted withinterview using a questionnaire to 40 mothers and 40 midwivesin the district Situbondo. Data is also collected throughsecondary data from the district health office Situbondo andhospital.Results: From the 40 respondents that had been interviewed,92.5% ask for help to providers, but as much as 7.5% ask forpartus help from traditional birth attendants. In addition, theJampersal still charged costs to maternal care to as many as12 people (30%). This is non-conforming to Jampersal policyof giving free maternal care. In Jampersal implementation inSitubondo, 50% of midwives have good commitment. While27.5% showed medium commitment and the remaining 22.5%is less committed. The magnitude of this commitment varies.Respondents with the age of 30-39 years shows excellentcommitment ( 55%), and those who work for 1-9 years arecommitted (50%). Socialization of Jampersal policy hasn’t beenoptimal. Jampersal is still not known by all pregnant womenyet. The term “free treatment” is confused with the health cardpolicy.Conclusion: There is a high trust level in pregnant womenwho asks for partus help (92.5%). Commitment of provider inrunning the Jampersal policy is still high. Jampersal socializationhasn’t reached the optimal level because people still do notunderstand the conditions of Jampersal.Suggestion: Since birth delivery by the traditional birth attendantsis still common, the midwife should work with traditionalbirth attendants in terms of infant care such as bathing, andgive incentives when collaborating in handling after partus.There is a need to improve midwife skills in detecting the riskof pregnancy and childbirth. Socialization Jampersal need toinvolve community leaders, and religion leaders.Keywords: Jampersal, pregnant women’ trust, Provider Commitment.